Silver nanoparticle coating on cotton fabric modified with poly(diallyldimethylammonium chloride). (2nd July 2016) - Peng, L.; Guo, R.; Lan, J.; Jiang, S.; Wang, X.
Abstract : Silver nanoparticles were coated on cotton fabric modified with poly(diallyldimethylammonium chloride) (PDDA). The synthesised silver nanoparticles were characterised by transmission electron microscopy and ultraviolet–visible (UV–Vis) spectroscopy. The silver nanoparticle coated cotton fabrics modified with PDDA were examined by X-ray photoelectron spectroscopy and scanning electron microscopy. The effects of concentration of PDDA in the pretreatment solution on colour characteristics and UV transmittance of the silver nanoparticle coated cotton fabrics modified with PDDA were investigated. Colour fastness of silver coated cotton fabrics modified with PDDA was also evaluated. The results show that the PDDA modified cotton fabrics are covered with dense silver nanoparticles. Colour strength of the silver nanoparticle coated cotton fabric modified with PDDA increases with the rise of concentration of PDDA in pretreatment solution. The incorporation of PDDA improves washing fastness of silver nanoparticle coated cotton fabrics.